Evaluasi Kebijakan Literasi Bahasa di Sekolah: Systematic Literature Review - Amandha, Mayzita Dwi; Sugiarto, Sugiarto; Takdir, Muh.; Mayasari, Linda Ika; Syam, Aldo Redho (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
Literacy policies in Indonesia have experienced significant development over the past decade through various national programs such as the National Literacy Movement (GLN), the School Literacy Movement (GLS), the Minimum Competency Assessment (AKM), as well as the strengthening of digital literacy, information literacy, and multilingual literacy. Nevertheless, various international surveys such as PISA show that the literacy achievement of Indonesian students is still at a low level. This condition underscores the importance of evaluating literacy policies as well as their implementation in educational institutions. This study aims to analyze literacy policies in Indonesia and evaluate the implementation of literacy programs in schools through a Systematic Literature Review (SLR) of 20 selected articles from a total of 150 initial articles sourced from Google Scholar and Scopus. The analyzed articles include national literacy policies, evaluations of literacy programs based on the CIPP model, digital literacy, information literacy, multilingual literacy, and the implementation of literacy in the Merdeka Curriculum. The SLR results show that national literacy policies have provided clear policy directions in strengthening the culture of literacy, but their implementation in schools faces various challenges such as limited facilities, low reading motivation, uneven teacher competencies, and minimal integration of literacy into learning. On the other hand, several literacy programs have been proven to improve reading ability, literacy interest, and 21st-century skills when supported by school management, parental support, and resource readiness. This study emphasizes the need for more comprehensive literacy policies, strengthening teacher capacity, providing adequate literacy facilities, and a continuous evaluation system to ensure the effectiveness of literacy policy implementation in schools.